Réponses

2014-03-13T21:54:52+01:00
A=(3x-5)² - (3x-5) (x+4)
a=9x
²-30x+25-(3x²+16x-5x-20)
a=9x²-30x+25-3x²-16x+5x+20
a=6x²-41x+45

 (3x-5)((3x-5) (x+4))
(3x-5)(3x²+16x-5x-16)
(3x-5)(3x²+11x-16)

2014-03-13T22:00:34+01:00
A) (3x-5) (3x-5) - (3x-5) (x+4)
= 9x² - 15x - 15x + 25 - (-3x-5) (x+4)
= 9x² -30x + 25 + 3x² -12x -5x -20
= 12x² - 47x +5
pour moi je trouve ce résultat pour le petit a)

b) (3x-5) [ (3x-5)-(x+4) ]
= (3x-5) (3x-5+x-4)
= (3x-5) (4x-9)
voila ce que je trouve au b)

c) Quand x = 1
(3 fois 1 -5) (4 fois 1-9)
= (3-5) (4-9)
= -2 x -5
=10
je ne suis pas sur

quand x=4.5
= (13.5 -5 ) (18-9)
=8.5 x 9
= 76.5
peu etre a vérifier